The glacial history of Tongariro and Ruapehu volcanoes, New Zealand - Eaves, Shaun (11703830) (2015)
Understanding the drivers and mechanisms of past, natural changes in Earth’s climate is a fundamental goal of palaeoclimate science. Recent advances in cosmogenic surface exposure dating and numerical glacier modelling have greatly improved the utility of geological glacial records for palaeoclimatic reconstruction. Here, I apply these techniques to investigate the timing and magnitude of late Quaternary mountain glacier fluctuations on Tongariro massif and Mt. Ruapehu volcanoes in central North Island, New Zealand (39°S). First, I constrain the local cosmogenic ³He production rate, in order to compare my subsequent ³He moraine chronologies with other well-dated palaeoclimate records. I present a new radiocarbon age for a large debris avalanche event on the northwest slopes of Mt. Ruapehu that occurred at 10.4-10.6 cal. ka BP. Cosmogenic ³He concentrations in surficial boulders deposited during this event are consistent with that predicted by a global compilation of similar production rate calibrations. Thus, I conclude that this globally compiled production rate is suitable for cosmogenic ³He exposure age calculations in New Zealand. Exposure ages from moraine boulders on both volcanoes constrain the timing of two periods of glaciation during the last glacial cycle, when the termini of valley glaciers reached c. 1200 m asl. The most recent of these events occurred between c. 31-17 ka, which corresponds with the global Last Glacial Maximum. During this period, the local equilibrium line altitude was depressed by c. 800-1100 m. Numerical model simulations of the glaciers, using a coupled energy balance/ice flow model, suggest that local atmospheric temperature was 4-7 °C colder than present. This palaeotemperature estimate is not greatly impacted by post-glacial topographic change on these active volcanoes. Surface exposure ages from a degraded lateral moraine on Tongariro massif indicate that an earlier period of glaciation, of similar extent to that at the LGM, culminated during Marine Isotope Stage 4. During the last glacial-interglacial transition (c. 18-11 ka), glacial retreat on Mt. Ruapehu was interrupted by a re-advance during the late-glacial (c. 15-11 ka). Exposure ages for this event exhibit some scatter, likely due to surface processes. Accounting for these processes with a topographic diffusion model yields a best-estimate age of 14-13 ka, corresponding to the Lateglacial reversal in New Zealand. Glacier model experiments indicate this re-advance resulted from a temperature lowering of 2.5-3.4 °C relative to present. Comparison with other proxy records suggests that this cooling was most pronounced during summer. Due to its lower elevation, it is unlikely that glaciers were present on Tongariro massif at this time. The results of this research provide the first direct age constraint and quantitative palaeoclimate reconstructions for late Quaternary glacier fluctuations in central North Island, New Zealand. The timing and magnitude of these changes are in good agreement with glacial records from the Southern Alps and South America. This suggests that glaciers in the southern mid-latitudes were responding to common climatic forcings at orbital- and millennial-timescales, during the last glacial cycle.